2022
DOI: 10.1001/jamanetworkopen.2022.3827
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cimetropium Bromide Use for the Detection of Gastric Neoplasms During Esophagogastroduodenoscopy

Abstract: Key Points Question Is the use of cimetropium bromide, an antispasmodic agent, associated with higher rates of detection of gastric neoplasms during esophagogastroduodenoscopy (EGD) screening? Findings In this cohort study of 67 683 participants who received EGD screening, the use of cimetropium bromide as premedication was associated with higher gastric neoplasm detection rates during EGD than nonuse. Lesions in the gastric body were detected more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…A recent propensity score-matched study in Korea showed that cimetropium bromide use was significantly associated with increased gastric neoplasm detection rates, especially for lesions in the stomach body (gastric neoplasm detection rate, 0.30% [cimetropium bromide users] vs. 0.19% [non-users]; p =0.02). 26 A Japanese study reported that premedication with scopolamine did not significantly increase the detection rate of upper GI neoplasia (upper GI neoplasia detection rate, 0.42% [scopolamine users] vs. 0.39% [non-users], p =0.89). 27 There is no objective classification for the measurement of peristalsis, and different individuals might have different responses to antispasmodic agents.…”
Section: Premedicationmentioning
confidence: 97%
“…A recent propensity score-matched study in Korea showed that cimetropium bromide use was significantly associated with increased gastric neoplasm detection rates, especially for lesions in the stomach body (gastric neoplasm detection rate, 0.30% [cimetropium bromide users] vs. 0.19% [non-users]; p =0.02). 26 A Japanese study reported that premedication with scopolamine did not significantly increase the detection rate of upper GI neoplasia (upper GI neoplasia detection rate, 0.42% [scopolamine users] vs. 0.39% [non-users], p =0.89). 27 There is no objective classification for the measurement of peristalsis, and different individuals might have different responses to antispasmodic agents.…”
Section: Premedicationmentioning
confidence: 97%
“…A study included 67,683 participants and found that gastric neoplasm detection rates were significantly higher in the group who received cimetropium bromide before EGD (63 participants [0.30%]) than the control group (39 participants [0.19%]; P = 0.02) 23 . This suggests that the use of antispastic agents may have a positive impact on lesion detection during EGD, but more research is needed.…”
Section: Risk Stratification Before the Proceduresmentioning
confidence: 99%
“…[31][32][33][34][35] The use of antispasmodics is a useful adjunct in reducing peristalsis that may obscure gastric views but the evidence on improving the detection of neo-plasms is limited and conflicting. 36,37 While fasting is a prerequisite for an endoscopic examination, expert recommendations on fasting relate to the risks of sedation and aspiration rather than the adequacy of mucosal visualization for cancer detection. 25,38 While these specific measures contribute to a highquality examination, their salutary effects could be subsumed under a more general measure of gastric mucosal visualization which may be more amenable to quality improvement.…”
Section: Mucosal Visualizationmentioning
confidence: 99%
“…Premedication with N‐acetylcysteine and simethicone improves mucosal visualization but has not been demonstrated to translate into an increase in the detection of gastric neoplasia 31–35 . The use of antispasmodics is a useful adjunct in reducing peristalsis that may obscure gastric views but the evidence on improving the detection of neoplasms is limited and conflicting 36,37 . While fasting is a prerequisite for an endoscopic examination, expert recommendations on fasting relate to the risks of sedation and aspiration rather than the adequacy of mucosal visualization for cancer detection 25,38 …”
Section: Mucosal Visualizationmentioning
confidence: 99%